The Supply Side of Marine Tourism Towards Sustainable Ecotourism: Case Study Of Tampora Beach, Situbondo - Zainul Hasan; Ihrom Caesar Ananta Putra; Dedy Wijaya Kusuma; Suwignyo Widagdo; Kun Afifah Nur Arifin (Universitas Muhammadiyah Jember, 2022)
This study aims to determine the factors influencing tourist visits to marine tourism at Tampora Beach, Situbondo. The analytical method used is multiple linear regression analysis. This study uses primary data obtained from surveys and interviews—sampling research with the accidental sampling method. The independent variables used are facilities, institutions, travel costs, and accessibility, while the dependent variable is tourist visits. The study found that the facilities, institutions, and accessibility of tourist objects greatly influenced tourist visits. However, in this study, the variable travel costs did not affect the number of tourist visits. Management of tourist destinations with complete facilities and infrastructure such as bathrooms, hotels, restaurants, and institutions (information and security centres) and accessibility (transportation and tourist routes) will increase the number of tourists. Offering this tourist attraction will influence the decision of tourists to visit a tour. It will directly impact increasing the number of tourist visits and the length of stay of tourists on these tours. Moreover, indirectly will affect improving the welfare of the community around tourism and regional income.